2018
DOI: 10.2967/jnumed.117.203570
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Nonprostate Cancers Using PSMA-Targeted Radiotracers: Rationale, Current State of the Field, and a Call to Arms

Abstract: Prostate-specific membrane antigen (PSMA) is a type II transmembrane glycoprotein that is highly overexpressed on prostate cancer epithelial cells and for which there is a growing body of literature examining the role of small-molecule and antibody radiotracers targeted against this protein for prostate cancer detection and therapy. Despite its name, PSMA is also expressed, to varying degrees, in the neovasculature of a wide variety of nonprostate cancers; indeed, the pathology literature is replete with promi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 133 publications
(91 citation statements)
references
References 72 publications
(144 reference statements)
0
90
0
1
Order By: Relevance
“…In light of the growing availability of 68 Ga-or 18 F-labeled PSMA-targeted imaging agents (19)(20)(21)(22), the number of molecular imaging specialists that routinely interpret PET scans with these compounds outside controlled clinical trials is expanding (23). However, numerous studies have reported pitfalls in the reading of PSMA-targeted PET studies, including studies of Paget disease, sarcoidosis, or nervous tissue such as ganglia (7-10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of the growing availability of 68 Ga-or 18 F-labeled PSMA-targeted imaging agents (19)(20)(21)(22), the number of molecular imaging specialists that routinely interpret PET scans with these compounds outside controlled clinical trials is expanding (23). However, numerous studies have reported pitfalls in the reading of PSMA-targeted PET studies, including studies of Paget disease, sarcoidosis, or nervous tissue such as ganglia (7-10).…”
Section: Discussionmentioning
confidence: 99%
“…Identical Target Lesion Included by 4 Readers. The identical target lesion was included by all 4 readers in 58 of 125 (46.4%) instances, with the majority of those findings being either LN (26, 44.8%) or bone lesions (19,32.8%). In 29 (50%) of those 58 target lesions, all 4 readers designated the identical PSMA-RADS score, with another 17 lesions (29.3%) having agreement by 3 readers and the remaining 12 (20.7%) having agreement by 2 readers.…”
Section: Target Lesion-and Compartment-based Interobserver Agreementmentioning
confidence: 99%
“…Its expression is elevated with increasing PCa stage and grade making it an excellent biomarker for staging, metastasis detection, and image‐guided interventions . PSMA is also expressed on the neovasculature of other types of carcinomas such as breast and thyroid, making it an important biomarker in the larger scope of cancer research as well …”
Section: Methodsmentioning
confidence: 99%
“…[4,6] PSMA is also expressed on the neovasculature of other types of carcinomas such as breast and thyroid, making it an important biomarker in the larger scope of cancerresearch as well. [18,19] Elucidation of the structure of the PSMA binding site using protein crystallography led to the development of small molecule inhibitors which included amide, phosphonate, and urea substrate analogues. [6,20,21] Amongt he most effective of these was as mall molecule synthesized by ap eptidomimetic urea linkage of lysine to glutamic acid in place of the naturallyo ccurring peptidea mide substrate.…”
mentioning
confidence: 99%
“…The most widely studied agent is the 68 Ga-labelled PSMA inhibitor Glu-NH-CO-NH-Lys(Ahx)-HBED-CC ( 68 Ga-PSMA) but in recent years 18 F-labelled ligands such as 2-(3-(1-carboxy-5-[(6-[ 18 F]fluoro-pyridine-3-carbonyl)-amino]-pentyl)-ureido)-pentanedioic acid ( 18 F-DCFPyL) have been developed which show advantages with respect to production amount, availability, clinical utility, and image resolution [3,4]. PSMA is also expressed by a variety of nonprostate cancers, often on the endothelium of tumor-associated neovasculature [5] and initial studies have explored the application of PSMA ligands in breast, lung, bladder, pancreatic and colorectal cancer, renal cell carcinoma and glioblastoma [6]. In a triple negative breast cancer xenograft the localization of PSMA was detected in the xenograft-associated endothelial cells as well as on the tumor cells [7].…”
Section: Introductionmentioning
confidence: 99%